Significance of lymph node metastasis in the survival of stage IV colorectal cancer by hematogenous metastasis - Han, Eon Chul; Kwon, Yoon-Hye; Park, Kyu Joo; Jeong, Seung-Yong; Kang, Sung-Bum; Oh, Jae Hwan; Heo, Seung Chul (Annals of surgical treatment and research, 2018)
Although lymph node (LN) metastasis is an important prognostic marker of colorectal cancer (CRC), the effect of LN metastasis on the survival of stage IV CRC is debated yet. LN status and survivals as well as clinicopathological features of synchronous stage IV CRC patients, operated for 8 years, were analyzed. Patients with hematogenous metastases were included only but those with peritoneal seeding or preoperative adjuvant therapy were not included. Total 850 patients were enrolled and 77 (9.1%) were without LN metastases (N0M1). N0M1 patients were older and have favorable pathological features including lower CEA than patients with LN metastasis (N + M1). The pathologically poor features accumulated with N stage progression within N + M1. N0M1 had better 5-year overall survival (OS) and disease free survival than N + M1. And 5-year OS's within N + M1 group were stratified and different according to N stage progression, although the effect of N stage progression is different according to curative resection or not. When compared with stage III, 5-year OS of N0M1 with curative resection was comparable to that of anyTN2aM0 and was better than anyTN2bM1. LN metastasis is a significant prognostic factor in stage IV by hematogenous metastasis, too. N stage progression accumulates pathologically poor prognostic factors. However, the effect on survival of each N stage progression differs depending on curative resection or not of the hematogenous metastases.